2001
DOI: 10.1054/bjoc.2000.1593
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity in the Hodgkin-Reed Sternberg cell line L1236

Abstract: Summary Hodgkin-Reed Sternberg cells are derived from germinal centre B-cells in most cases. Somatic mutations affecting their rearranged immunoglobulin genes were detected, rendering potential functional rearrangements non-functional. Under physiological conditions such cells would be designated to undergo apoptosis within the germinal centre. In search for the specific transforming event that prevents Hodgkin-Reed Sternberg cells from programmed cell death, cytogenetic analyses were broadly performed but did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In cancers, 6p copy number neutral (CN) LOH is a very common mechanism of immune surveillance escaping, as lost of 6p arm determines the lack of expression of HLA class I alleles on cell surface, thus favoring the escape of cells from autologous attack of cytotoxic T cells [ 40 43 ]. Hodgkin and Reed-Stenberg cells in HL can also frequently use this mechanism to evade immune surveillance [ 44 ]. In our study, using NIPT-based technologies for liquid biopsy analysis, we demonstrated that whole chromosome 6 loss or 6p LOH are common alterations in hematological malignancies, not only in those with an immune-mediated pathogenesis, such as acquired bone marrow failure syndromes and HL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancers, 6p copy number neutral (CN) LOH is a very common mechanism of immune surveillance escaping, as lost of 6p arm determines the lack of expression of HLA class I alleles on cell surface, thus favoring the escape of cells from autologous attack of cytotoxic T cells [ 40 43 ]. Hodgkin and Reed-Stenberg cells in HL can also frequently use this mechanism to evade immune surveillance [ 44 ]. In our study, using NIPT-based technologies for liquid biopsy analysis, we demonstrated that whole chromosome 6 loss or 6p LOH are common alterations in hematological malignancies, not only in those with an immune-mediated pathogenesis, such as acquired bone marrow failure syndromes and HL.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, using NIPT-based technologies for liquid biopsy analysis, we demonstrated that whole chromosome 6 loss or 6p LOH are common alterations in hematological malignancies, not only in those with an immune-mediated pathogenesis, such as acquired bone marrow failure syndromes and HL. Moreover, losses of the long arm of chromosome 6 are frequently in solid tumors, including melanoma, renal cell carcinoma, salivary gland adenocarcinoma, or ovarian carcinoma, and in hematologic malignancies, such as acute lymphoblastic leukemia and B-cell lymphomas, occurring in at least 32 and 7% of patients, respectively [ 44 ]. Among B-cell lymphomas, deletions of 6q are commonly observed in CLL, MM, DLBCL, and FL, in which are associated with adverse clinical outcomes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) at the long arm of chromosome 9 has been demonstrated in several types of lymphoid malignancies, including diffuse large B-cell lymphoma, 1-3 follicular lymphoma, 4 multiple myeloma, 5 mantle cell lymphoma, 6 Hodgkin lymphoma, 7 acute lymphoblastic leukemia, 8,9 and chronic lymphocytic leukemia. 10 Some of these studies have implicated the 9q32-33 region as the prevailing target for deletion, suggesting that this region harbors an important tumor suppressor gene for lymphoproliferative cancers.…”
mentioning
confidence: 99%